Pumps - Stewart, Harry L. (Macmillan, 1991)
Pumps and hydraulic equipment are now used in more facets of industry than ever before. Whether you are a pump operator or you encounter pumps and hydraulic systems through your work in another skilled trade, a basic knowledge of the practical features, principles, installation, and maintenance of such systems is essential. You'll find it all here, fully updated with real-world examples and 21st-century applications.